2011
DOI: 10.1097/pas.0b013e31821a7f3e
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic Lipid Accumulation in Apocrine Carcinoma of the Breast Evaluated With Adipophilin Immunoreactivity

Abstract: Although apocrine carcinoma is a distinct histologic entity, there is no immunohistochemical marker to confirm apocrine differentiation with high sensitivity and specificity, and its differential cytologic characteristics are still not fully clarified. Despite the foamy cytoplasm of some apocrine carcinomas and the existence of lipid in the normal apocrine gland, intracytoplasmic lipid in apocrine carcinomas has not been fully explored. By using immunohistochemistry for adipophilin, which is a specific marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Moreover, many epithelioid melanomas with prominent nucleoli that presented with high ADP expression were associated with an abundant eosinophilic cytoplasm ( n = 15; 57.7%) (Fig. B), which was morphologically reminiscent of ADP‐positive carcinomas of the breast and lung . As discussed previously, there was no correlation between high ADP expression and histological subtype.…”
Section: Resultsmentioning
confidence: 56%
“…Moreover, many epithelioid melanomas with prominent nucleoli that presented with high ADP expression were associated with an abundant eosinophilic cytoplasm ( n = 15; 57.7%) (Fig. B), which was morphologically reminiscent of ADP‐positive carcinomas of the breast and lung . As discussed previously, there was no correlation between high ADP expression and histological subtype.…”
Section: Resultsmentioning
confidence: 56%
“…As it is unclear as to the number of lipid-containing cells required to confirm the diagnosis of lipid-rich carcinoma, the definition of the tumor is not yet clearly established (3). Certain studies have suggested that >90% of the neoplastic cells should contain lipid droplets in lipid-rich carcinoma (2,7). The origin of the lipids in the neoplastic cells is also not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of lipid-rich carcinoma is still not exactly established, because it is not clear, how many cells are supposed to be lipid containing to confirm the diagnosis [6]. Some authors suggested that lipid-rich carcinoma should contain lipid droplets in more than 90% of the neoplastic cells [1, 7, 8]. Also the origin of the lipids in the neoplastic cells is matter of discussion.…”
Section: Discussionmentioning
confidence: 99%
“…None of the apocrine and nonapocrine carcinomas had positive staining of adipophilin in more than 90% of the cells, thus the criteria for lipid-rich carcinoma was not fulfilled. Their immunohistochemical study suggested that lipid-rich carcinomas and apocrine carcinomas are closely related [7]. …”
Section: Discussionmentioning
confidence: 99%